European SME policy: Recommendations for a growth-oriented agenda - Klaus-Heiner Röhl (Institut der deutschen Wirtschaft (IW), 2017)
The economic policy of the European Union influences the almost 23 million small and medium-sized companies in the 28 Member States in a variety of ways. Yet, there exists no coherent EU policy on small and medium-sized enterprises. With the Small Business Act of 2008, small and medium-sized enterprises received greater attention, but this primarily applies to start-ups and small companies. As a result of the European debt crisis, start-ups and established small and medium-sized companies have returned into focus for policy-makers in Brussels. They hope that SMEs create more jobs and growth. Despite this, the concerns of SMEs are still not at the heart of economic policy and regulation. That is also clear when looking at the EU budget and its high agricultural expenditures. It is particularly problematic that larger family companies with over 250 employees or a turnover of 50 million euro are regarded as large companies. They are treated in the same way as big corporations. A better targeted EU policy on SMEs should reduce red tape for companies and include family companies that have grown beyond the defined SME thresholds. Additionally, it should recognise medium-sized industrial enterprises as key partners in implementing the objective of reinvigorating European industry by 2020.
Keywords: 330